PS-BPC06-10: FATTY LIVER INDEX AND CARDIOVASCULAR RISK IN HYPERTENSIVE PATIENTS. (January 2023) - Siafi, Eirini; Andrikou, Ioannis; Thomopoulos, Costas; Konstantinidis, Dimitrios; Kakouri, Niki; Tatakis, Fotis; Kariori, Maria; Filippou, Christina; Zamanis, Ioannis; Manta, Eleni; Drogkaris, Sotirios; Liatakis, Ioannis; et al.
Abstract : Objective: The prevalence of nonalcoholic fatty liver disease (NAFLD) has been increasing rapidly worldwide affecting 25–30% of population. Fatty liver index (FLI) is a validated marker of NAFLD and can be used as a screening tool for hepatic steatosis. The purpose of the study was to evaluate the relationship between FLI and the risk of major cardiovascular events in hypertensive patients. Design and method: 903 hypertensive patients without history of cardiovascular disease participated in the study (mean age 52.7 ± 11.4 years; males 55%; baseline clinic BP 149.8 ± 15.2/95.5 ± 10.1 mmHg). Participants were prospectively evaluated for a mean follow-up period of 6.0 ± 3.3 years with at least one annual visit. The diagnosis of NAFLD was based on FLI and consequently patients were divided in two groups according to the presence of NAFLD. The primary endpoint was a composite of major cardiovascular events. Results: The incidence of cardiovascular events during the follow up was 8.5% (n = 77). Patients without NAFLD (n = 625) had better BP control compared to their counterparts with NAFLD (n = 278) during follow up (43% vs 33%, p = 0.02). A Cox-regression analysis indicated that age (hR 1.09 CI 1.04–1.13, p < 0.01), smoking (hR 2.4 CI 1.1–5.2, p = 0.03) and FLI (hR 2.7 CI 1.9–4.1, p < 0.001) were significant independent determinants of the outcome. The presence of NAFLD at baseline visit was also a significant independent determinant of the outcome (hR 5.2 CI 2.4–11.1, p < 0.001). Conclusions: In conclusion, FLI has an independent prognostic value for the incidence of cardiovascular events in hypertensive patients. Therefore, it could be useful in identifying patients at higher risk of cardiovascular events. Further studies will clarify whether the early treatment of NAFLD could reduce the incidence of cardiovascular disease.